2012
DOI: 10.1136/jmedgenet-2012-101257
|View full text |Cite
|
Sign up to set email alerts
|

An Italian association study and meta-analysis with previous GWAS confirmWNT4,CDKN2BASandFN1as the first identified susceptibility loci for endometriosis

Abstract: We confirm WNT4, CDKN2BAS and FN1 as the first identified common loci for endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 21 publications
2
62
2
3
Order By: Relevance
“…In addition, as reported in a recent study by Pagliardini et al [7], more severe stages of the disease were associated with a higher frequency of the risk allele G of rs1333049 in the CDKN2BAS locus.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, as reported in a recent study by Pagliardini et al [7], more severe stages of the disease were associated with a higher frequency of the risk allele G of rs1333049 in the CDKN2BAS locus.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, based on the results of few genome-wide association studies (GWAS), few genetic susceptibility loci have been identified as associated robustly with the disease, thus opening a new era in the context of the discovery of genes predisposing to endometriosis [5,6]. Our replication analysis in an Italian population considering 4 of these polymorphisms allowed us to confirm 3 of these gene variants, rs7521902 close to WNT4 , rs1250248 within the fibronectin 1 ( FN1 ) gene and rs1333049 in the CDKN2BAS locus as common loci involved in the susceptibility to endometriosis [7]. However, despite the natural excitement emerging from these novel findings, mechanisms underlying genotype-phenotype relationships are totally unknown so far.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The relationship between rs2235529 and endometriosis was previously observed in North American and Chinese Han women [9,19]. Similarly, the rs7521902 was associated with endometriosis susceptibility in British, Australian, Italian, and Japanese women [21,22,8], but not in Belgian women [23]. The lack of an association between these two polymorphisms and endometriosis may be caused by the different genetic backgrounds of the Brazilian cohort that is considered as a highly admixed population [24].…”
Section: Discussionmentioning
confidence: 57%
“…The three replication studies (Pagliardini et al, 2013(Pagliardini et al, , 2015Sundqvist et al, 2013) performed to date have only replicated association of rs7521902 (p = 5.6 × 10 −3 ; Pagliardini et al, 2013) and rs10859871 (p = 6.9 × 10 −5 ; Pagliardini et al, 2015) with endometriosis. Inherently hidden fine stratification among different populations of similar ancestry, which is often difficult to tease apart, power, and possible variations in disease definition and/or classification may have contributed to these inconsistent results.…”
mentioning
confidence: 99%